Muhammad Asad Shahab and the role of the press during Indonesian national revolution, 1945-1949 - Jeffry Muhammad Hafis (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
This study is an attempt to explain the role of the press during Indonesian national revolution 1945-1949. This study also analyzes Muhammad Asad Shahab's historical background, his formative years and his contribution in defending Indonesia's independence which declared on August 17, 1945. In order to explain and analyze these aims, the researcher used the historical and analytical approach. The study finds the importance of journalism in supporting Indonesian struggle against the return of Dutch colonialism. The news of Indonesian independence needed to be widely disseminated to the Indonesian society and abroad. Accordingly, the study suggests that the presence of the press in order to form opinion, spirit and optimism at the time of revolution was very important for these needs. In addition to the fighting spirit and optimism of the local society, the presence of colonial threat and Indonesian struggle to defend its independence needed to be disseminated to other countries so that it could be known, acknowledged and gained supports. Also, based on the traces of the press in Jakarta, the study finds that Arabian Press Board (APB), which was founded by M. Asad Shahab and his colleagues, is the only press that specifically spread the news both nationally and internationally. Moreover, as shown by our research, APB's news about Indonesian struggles that spread abroad, especially to the Middle East, as well as its reports sent to the Arab League secretary-general, had a strong relationship with Egypt's de facto recognition of Indonesia's independence in 1947, followed by some other countries. The study comes to the conclusion that through the press, M. Asad Shahab had contributed to safeguard Indonesian independence.